Pragmatic Approaches to Drama Studies in Communication on the Ancient Stage - Martin, Gunther; Iurescia, Federica; Hof, Severin; Sorrentino, Giada (The Language of Classical Literature, 2020)
This volume collects papers on pragmatic perspectives on ancient theatre. Scholars working on literature, linguistics, theatre will find interesting insights on verbal and non-verbal uses of language in ancient Greek and Roman Drama. Comedies and tragedies spanning from the 5th century B.C.E. to the 1st century C.E. are investigated in terms of im/politeness, theory of mind, interpersonal pragmatics, body language, to name some of the approaches which afford new interpretations of difficult textual passages or shed new light into nuances of characterisation, or possibilities of performance. Words, silence, gestures, do things, all the more so in dramatic dialogues on stage. Readership: Academics and advanced students interested in ancient Greek and Roman drama, historical pragmatics, drama and performance, linguistics, narratology, literary interpretation of dramatic genres.